Pitch accents of monophthongs in High Lithuanian (Utena subdialect): historical survey and experimental investigation - Švageris, Evaldas (Baltistica, 2018)
The present paper deals with the question of whether there is an acoustic basis for pitch accent distinction in High Lithuanian (i.e. in Utena subdialect). First, a historical survey was conducted in which theoretical frameworks of Kuršaitis, Baranauskas, Jaunius were discussed. In addition, the data from experimental studies were taken into account. The second part of this article deals with a new experimental investigation in which both tone sustainability coefficient and intensity extrema of long stressed vowels were estimated. In comparison to other dialects, none of these parameters appeared to be of great significance. On the basis of these results a conclusion that there is no reliable theoretical or experimental basis for the pitch accent functionality in Utena subdialect might be drawn. The cause of such prosodic process might be explained by a significant reduction in vowel quantity.
Keywords: Lithuanian; East Aukštaitian (East High Lithuanian) dialect; Utena subdialect; acoustic phonetics; sustainability coefficient; pitch accent; long vowels